2020
DOI: 10.1186/s12866-020-02054-5
|View full text |Cite
|
Sign up to set email alerts
|

Altitude influences microbial diversity and herbage fermentation in the rumen of yaks

Abstract: Background Rumen microbiota in ruminants are vital for sustaining good rumen ecology, health, and productivity. Currently, limited information is available regarding the response of yaks (Bos grunniens) to fluctuating environments, especially the rumen microbiome. To address this, we investigated the diet, rumen bacterial community, and volatile fatty acids (VFA) of rumen fluid of yaks raised in the great Qinghai-Tibet plateau (QTP) at 2800 (low altitude, L), 3700 (middle altitude, M), and 4700 m (high altitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 69 publications
7
56
0
1
Order By: Relevance
“…In this study, Bacteroidetes and Firmicutes were the most predominant bacterial phyla in the rumen of Tibetan sheep, corroborating the results of previous studies on Tibetan sheep (38,39), cattle (40), sheep (41), yaks (5,9,12), goats (42), and pikas (43), and indicating that these bacteria play an important role in the ecology and function of the mammalian gastrointestinal tract. Kim et al (44) conducted a meta-analysis of all selected 16S rRNA sequences stored in the NCBI database to summarize the distribution of rumen bacteria in major domestic animals and found that the proportions of Bacteroidetes and Firmicutes were approximately 31% and 56%, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, Bacteroidetes and Firmicutes were the most predominant bacterial phyla in the rumen of Tibetan sheep, corroborating the results of previous studies on Tibetan sheep (38,39), cattle (40), sheep (41), yaks (5,9,12), goats (42), and pikas (43), and indicating that these bacteria play an important role in the ecology and function of the mammalian gastrointestinal tract. Kim et al (44) conducted a meta-analysis of all selected 16S rRNA sequences stored in the NCBI database to summarize the distribution of rumen bacteria in major domestic animals and found that the proportions of Bacteroidetes and Firmicutes were approximately 31% and 56%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Between the collection of samples, the oral tube was thoroughly cleaned with clean water, and the first 50 mL samples of each yak will be discarded to ensure that it is not contaminated by previous animals and its own saliva. The sample pH was immediately measured using a pH meter (Model 206-pH2, Testo, Germany), as previously described ( 5 , 9 , 12 ). The rumen-fluid samples were used for VFA testing, ammonia nitrogen (NH 3 -N) concentration analysis, and DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These ruminants are resilient, in that they live and thrive in a hypoxic environment (oxygen content: 14.9~11.44%), which is cold (annual average temperature under 0~10 °C) and on a high plateau (3000~6000 m), with no guarantee of sufficient food. Their ability to adapt to such harsh environmental factors is facilitated by their large lungs, large heart, and efficient foraging and energy metabolism [ 14 ], as well as their gut microbiota which contributes significantly to live at a high altitude; also, a significant difference of microbiota was found between yaks in high and low plateaus [ 15 , 16 ]. The microbiota is generally recognized to play an important role in the functionality of immune systems, regulating intestinal motility, gut barrier homeostasis, and nutrient metabolism [ 17 ].…”
Section: Introductionmentioning
confidence: 99%